Evaluating the Prevalence of Dental Anomalies through Panoramic Radiographs in a Sample of Iranian Population During 2016 to 2020 - Narges Arya; Aslan Rafie; Rahim Tahmasebi; Vahid Akheshteh; Elahe Salmani (Journal of Mashhad Dental School, 2023)
Background: Dental anomalies can lead to malocclusions, compromise aesthetics, complicate endodontic procedures and tooth extraction. The presence of dental anomalies can predispose the individual to other oral and dental diseases.  The aim of this study was to investigate the prevalence of dental anomalies of permanent dentition in a sample of Iranian population.Material and Methods: Through this cross-sectional study, panoramic radiographs which were taken from September 2016-2020 were retrieved form the archived files of a private radiographic center in Bushehr, Iran. Radiographs of individuals with permanent dentition were selected, and a random sample was obtained using a non-randomized cluster sampling method. Radiographs were evaluated by a single oral and maxillofacial radiologist, and dental anomalies were identified and categorized. Descriptive statistics were presented as frequency, mean and standard deviation. Chi-square test was used and significance level was set at 0.05.Results: A total of 4962 radiographs were evaluated; 913 cases (18. 40%) had at least one dental anomaly. Abnormalities such as dens in dent (10. 3%), congenital missing (3. 35%) and impaction (2. 64%) were the most prevalent. The permanent left maxillary lateral incisor was the most common tooth in terms of prevalence of dental anomalies. The prevalence of dental anomalies in males was significantly higher than females (P= 0.03)Conclusion: Anomalies in morphology, number especially dens in dente and missing were the most common anomalies in the investigated population. The prevalence of dental anomalies was significantly higher in the maxilla and especially in the lateral incisors. Therefore, early identification and treatment is necessary in order to prevent the complications caused by these anomalies.